Beispiel Nr: 04
$ \text{Gegeben: } \\ P: y=a_1x^{2}+b_1x+c_1 \qquad g:y=mx+t\\ \text{Gesucht:Schnittpunkte zwischen Parabel und Gerade} \\ \text{Parabel-Gerade}\\ \textbf{Gegeben:} \\ p: y==-\frac{1}{2}x^2+x+2 \qquad g: y== \frac{1}{2}x-3 \\ \\ \textbf{Rechnung:} \\f\left(x\right)=-\frac{1}{2}x^2+x+2\qquad g\left(x\right)= \frac{1}{2}x-3\\ \bullet \text{Schnittpunkte zwischen zwei Funktionen} \\ f\left(x\right)=g\left(x\right) \\-\frac{1}{2}x^2+x+2= \frac{1}{2}x-3 \\ -\frac{1}{2}x^2+x+2-( \frac{1}{2}x-3)=0\\ \begin{array}{l|l|l} \begin{array}{l} \text{a-b-c Formel}\\ \hline \\ -\frac{1}{2}x^{2}+\frac{1}{2}x+5 =0 \\ x_{1/2}=\displaystyle\frac{-\frac{1}{2} \pm\sqrt{\left(\frac{1}{2}\right)^{2}-4\cdot \left(-\frac{1}{2}\right) \cdot 5}}{2\cdot\left(-\frac{1}{2}\right)} \\ x_{1/2}=\displaystyle \frac{-\frac{1}{2} \pm\sqrt{10\frac{1}{4}}}{-1} \\ x_{1/2}=\displaystyle \frac{-\frac{1}{2} \pm3,2}{-1} \\ x_{1}=\displaystyle \frac{-\frac{1}{2} +3,2}{-1} \qquad x_{2}=\displaystyle \frac{-\frac{1}{2} -3,2}{-1} \\ x_{1}=-2,7 \qquad x_{2}=3,7 \end{array}& \begin{array}{l} \text{p-q Formel}\\ \hline \\ -\frac{1}{2}x^{2}+\frac{1}{2}x+5 =0 \qquad /:-\frac{1}{2} \\ x^{2}-1x-10 =0 \\ x_{1/2}=\displaystyle -\frac{-1}{2}\pm\sqrt{\left(\frac{\left(-1\right)}{2}\right)^2- \left(-10\right)} \\ x_{1/2}=\displaystyle \frac{1}{2}\pm\sqrt{10\frac{1}{4}} \\ x_{1/2}=\displaystyle \frac{1}{2}\pm3,2 \\ x_{1}=3,7 \qquad x_{2}=-2,7 \end{array}\\ \end{array}\\ \\ \text{Schnittpunkt }1\\ f(-2,7)=-4,35\\ S(-2,7/-4,35)\\\\ \text{Schnittpunkt }2\\ f(3,7)=-1,15\\ S(3,7/-1,15)\\$